The slope of first line is m 1= ( 1 - 0 ) / ( - 2 - ( - 6 ) );
m = 1 / 4 ;
Because the second line is perpendicular to the first line, m2 * m1 = - 1 ;
m2 * ( 1 / 4 ) = -1;
m2 = - 4 ;
The equation of the second line is : y - 3 = ( - 4 )( x - 2 );
y - 3 = -4x + 8 ;
y = -4x + 11.
The algebraic expression uses the terms to denote symbols
sum of means addition
difference of means subtraction
product of means multiplication
quotient of means division
Here we have the term 6x
which actually means 6 times x or
6 multiplied by x
hence by multiplication we use the word product of
so we have the product of 6 and a number as our right answer
The base price of the iphone is $350 and additiobal charge of a month is $67. So additional charge for p months is $67p.
Determine the equation for total cost of iphone after p momths.
Answer:
3+2=5
5+2=7
Step-by-step explanation:
the square is 7 mass because from 3 to 5 the numbers increase by 2 so I add 5 and 2
Answer:
A
Step-by-step explanation:
An equation in the form y=kx represents something increasing at a constant <u>rate</u>